2003
DOI: 10.1109/tnn.2003.811559
|View full text |Cite
|
Sign up to set email alerts
|

A study of pattern recovery in recurrent correlation associative memories

Abstract: Abstract-In this paper, we analyze the recurrent correlation associative memory (RCAM) model of Chiueh and Goodman. This is an associative memory in which stored binary memory patterns are recalled via an iterative update rule. The update of the individual pattern-bits is controlled by an excitation function, which takes as its arguement the inner product between the stored memory patterns and the input patterns. Our contribution is to analyze the dynamics of pattern recall when the input patterns are corrupte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…For notational convenience, let rank . Hence, the total number of votes received by pattern is given by (38) The probabilities , , can be computed from training data by running trial simulations. If no training data is available, the following heuristic setting is found to be Fig.…”
Section: B Statistical Interpretation Of the Weightsmentioning
confidence: 99%
See 3 more Smart Citations
“…For notational convenience, let rank . Hence, the total number of votes received by pattern is given by (38) The probabilities , , can be computed from training data by running trial simulations. If no training data is available, the following heuristic setting is found to be Fig.…”
Section: B Statistical Interpretation Of the Weightsmentioning
confidence: 99%
“…Note that (38) shows how the local probabilities are combined to produce a global measure that is the target pattern. Again, the combination scheme is the simple summing given in (34) (the only difference is that the scaling factor has been dropped here).…”
Section: B Statistical Interpretation Of the Weightsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this network, the convergence time is almost unaffected by the number of stored vectors, hence, while space complexity is still , the recall time is independent of . When the nonlinear function is an exponential, we obtain the exponential correlation associative memory (ECAM), which has been deeply investigated both analytically and through simulations by several authors [13]- [18]. It has been shown that the ECAM can reach the capacity of an ideal AM, which is exponential with respect to the length of memory vectors [16].…”
Section: Introductionmentioning
confidence: 99%